Encapsulated saponin by ferritin nanoparticles attenuates the murine pneumococcal pneumonia. (November 2022) - Safdarpour, Saba; Eftekhari, Zohre; Eidi, Akram; Doroud, Delaram
Abstract: Streptococcus pneumonia is classified as a gram-positive bacterial pathogen that causes asymptomatic or symptomatic respiratory infections. This study aimed to evaluate the effects of designed encapsulated saponin by ferritin nanoparticles in the healing progression of experimental bacterial pneumonia. The saponin encapsulated by ferritin followed the disassembly-reassembly process. Pneumonia was induced by the preparation of Streptococcus pneumonia. A total of 50 NMRI mice were divided into control, pneumonia, pneumonia + ferritin, pneumonia + saponin, and pneumonia + encapsulated saponin by ferritin nanoparticles (Nano Saponin) groups. ELISA, Real-time PCR, and Western blotting were used to measure sera IL-4 level, tumor necrosis factor-alpha ( Tnf-α ), and protein cyclooxygenase-2 (COX-2) gene expression, respectively. COX-2 protein expression, Tnf-α gene expression, and serum levels of IL-4 reduced compared to the pneumonia group. The histopathology results revealed that the rates of inflammation, mucus secretion, pulmonary hemorrhage, thickening of the alveoli wall, and secretion of inflammatory cells were lower in the Nano Saponin group than in the other groups. This study suggests that Glycyrrhiza glabra saponin and encapsulated saponin by ferritin nanoparticles oral consumption with anti- Tnf-α effect besides decreasing protein expression of COX-2 allows mice with pneumonia to recover. Graphical abstract: Image 1 Highlights: Many ingredients from the medicine plants possess anti-inflammatory effect in induced pneumonia. Saponin, Glycyrrhiza glabra extraction, was encapsulated by ferritin nanoparticles exert anti-inflammatory function via regulating multiple pathways. Results showed that Saponin and encapsulated saponin by ferritin nanoparticles decrease IL-4, Cox2 protein level, and gene expression of TNF-alpha.